Partial automation of the seismic to well tie with the matching region estimation and segmented global optimization - Silva, Rafael da Costa (Universidade Federal de São Carlos, 2023)
Geophysical interpretation plays a fundamental role in the oil and gas exploration domain. Various geophysical methods can be employed to extract information about the geological configuration of rocks. The well-to-seismic tie, which involves matching well log profiles with observed seismograms, is a crucial activity in the processing and interpreting of seismic amplitudes. During the exploration phase, the seismic tie process helps the interpreter to understand the well region's seismic wavelet and the time-depth relationship. However, data noise and inherent uncertainties make the seismic tie time-consuming. This way, we propose a significant automation of the seismic tie process that estimates the probable alignment region and automatically aligns the seismic traces through segmented global optimization. The alignment region is estimated based on the velocity profile and alignment using the Dynamic Time Warping (DTW) algorithm. The three proposed methods accurately estimated the well base position in the seismic trace for most of the tested wells. Our approach performs the segmentation of the tying process by utilizing the time-depth relationship obtained from the initial alignment of synthetic and seismic traces using Constrained DTW. The segmentation of the Differential Evolution (DE) tying process increased the final correlation in all tested wells, with four achieving a correlation higher than 70% without causing unrealistic velocity variations.
Automação parcial da amarração poço sísmica com estimatição da região de alinhamento e otimização global segmentada.
Keywords: Amarração sísmica; Automação; Segmentação poço-sísmica; DTW; Otimização global; Região de amarração; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO